Analysis and Research of Computer Physique Evaluation Technology on Students' Lifelong Sports Consciousness. Issue 3 (October 2020) - Tang, Wen
Abstract: The evaluation system of physical fitness test in colleges and universities should attach importance to the education of lifelong physical education consciousness with computer physique evaluation technology, the education of lifelong physical education skills with test data, and promote students to change from passive training to active exercise. Through the guidance of thought intervention and skill intervention after the test, the goal of lifelong physical education can be achieved. Lifelong sports consciousness has its rich connotation and scope, and has a close relationship with college physical fitness evaluation system. There is a long way to go in the education of Cultivating College Studentship consciousness.